Analisis Keterampilan Guru Membuka dan Menutup Pelajaran Fikih dalam Meningkatkan Keaktifan Belajar Siswa MA Al Mufid Teluk Pandan - Hamdani; Anria, Reni (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
The background of this research is that there are some students who are less active, less enthusiastic and less serious in participating in the learning process, the importance of applying skills to open and close lessons in the learning process and the importance of increasing student learning activity to achieve learning goals. The purpose of this study was to describe the theacher’s skills in opening and closing Fiqh learning in increasing student learning activeness and knowing student learning activeness based on the teacher’s skills in opening and closing Fiqh learning. This type of research used is qualitative. By using data collection techniques in the form of observation, interviews and document review. Test the credibility of the data through data triangulation and data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results of this study indicate that the teacher has implemented the skills of opening and closing lessons well by carrying out each component in opening and closing lessons, with the implementation of these components students experience an increase in active learning students become more active both asking questions and expressing opinions during the learning process. The conclusion from this research is that the teacher has carried out the skills of opening and closing lessons in the Fiqh learning process, but there are several indicators in the opening and closing components of lessons that are rarely even seen being used by teachers, such as the use of assistive devices, apperception activities and follow-up at the end of learning that are not routinely carried out.